ION-IMPRINTED POLY(NITROSONAPHTOL-FORMALDEHYDE) WITH MAGNETITE CORE FOR PRECONCENTRATION IN CD(II) ION ANALYSIS - RIDHO ARROSYAD (NIM:10514040), ZAENUR
Cadmium is a metal that is harmful to the environment because it can not be degraded by microorganisms so that when entered in the human body will accumulate. In small quantities, cadmium has toxic effects and carcinogenic to the human body. The cadmium content can be analyzed using atomic absorption spectrophotometry, but is not sensitive for cadmium in low concentration. The solid phase extraction technique for preconcentration using Ion Imprinted Polymer (IIP) can solve that problem. In this research, IIP has been synthesized in form of Cd(II)-ion imprinted poly(nitrosonapthole-formaldehyde) with magnetite-core (IIPM) for preconcentration of cadmium ions in water. Characterization with infrared spectrocopy showed absorption at 3448 cm-1, 1463 cm-1, 1085 cm-1, and 588 cm-1 that indicating the presence of functional groups -OH, C-H methylene (-CH2-), -NO, and Fe-O on IIPM. Characterization with transmission electron microscopy shows the process of surface imprinting of the polymer on the surface of the magnetite core has been successfully performed. Evaluation of IIPM adsorption parameters was done by batch method and showed that IIPM worked optimally at pH 5 with 20 minutes of contact time. IIPM has a maximum adsorption capacity at 9.06 mg/g by following the pseudo second order adsorption kinetics and Langmuir adsorption isotherm. IIPM is shown to be selective against Cd(II) ions in the presence of Zn(II) and Pb(II) ions because they have S>1 values and are not selective in the presence of Cu(II) ions. The adsorption-desorption process provides a recovery value of about 100% with preconcentration or without preconcentration. IIPM was applied for analysis of Cd(II) ion content in river water samples and found that Cd(II) ion content in river water was 51.39 ppb.